Evaluating Weight Loss With Semaglutide in Elderly Patients With Type II Diabetes. (February 2023) - Huynh, Grace; Runeberg, Haley; Weideman, Rick
Background: Semaglutide is an effective agent indicated for type II diabetes mellitus (T2DM) treatment and weight management. It is unknown if the magnitude of weight loss differs significantly between nonelderly (18-64 years old) and elderly (≥65 years old) patients diagnosed with T2DM.Objective: To determine whether there is a significant difference in percent weight loss between elderly and nonelderly Veterans diagnosed with T2DM and initiating semaglutide.Methods: This institutional review board-approved retrospective cohort study conducted at the VA North Texas Health Care System included adult Veterans with T2DM initiating semaglutide. Veterans with medications, procedures, or conditions that could significantly affect weight were excluded. The primary endpoint was the difference in percent weight loss 3 months after initiating semaglutide. Secondary endpoints were differences in percent weight loss at 6 months and differences of kilogram weight loss at 3 and 6 months. Safety outcomes were significant adverse drug events (ADEs) associated with semaglutide.Results: In total, 177 Veterans were analyzed (n = 111 elderly, n = 66 nonelderly). For the primary endpoint, elderly Veterans lost a mean of 2.02% body weight versus 2.25% in the nonelderly with a mean difference of 0.23% (95% CI, –1.03% to 1.48%; P = 0.72). Secondary endpoints were also not statistically significant. Significant ADEs were gastrointestinal-related, leading to drug discontinuation or dose reduction.Conclusion: Weight loss differences between elderly and nonelderly Veterans diagnosed with T2DM initiating semaglutide were not statistically significant. Age may not be a robust predictor of semaglutide's influence on weight.